The HopQ-CEACAM Interaction Controls CagA Translocation, Phosphorylation, and Phagocytosis of Helicobacter pylori in Neutrophils - Ina-Kristin Behrens (American Society for Microbiology, 2020)
ABSTRACT The cag type IV secretion system (cag-T4SS) of Helicobacter pylori exploits specific cellular carcinoembryonic antigen-related cell adhesion molecules (CEACAMs), such as CEACAM1, -3, -5, and -6, as cellular receptors for CagA translocation into human gastric epithelial cells. We studied the interaction of H. pylori with human CEACAM1, CEACAM3, and CEACAM6 receptors (hCEACAMs) expressed on myeloid cells from CEACAM-humanized mice. Human and CEACAM-humanized mouse polymorphonuclear neutrophils (PMNs) allowed a specific HopQ-dependent interaction strongly enhancing CagA translocation. Translocated CagA was tyrosine phosphorylated, which was not seen in wild-type (wt) murine neutrophils. In contrast, human or murine bone marrow-derived macrophages and dendritic cells (DCs) revealed a low hCEACAM expression and bacterial binding. CagA translocation and tyrosine-phosphorylation was low and independent of the HopQ-CEACAM interaction. Neutrophils, but not macrophages or DCs, from CEACAM-humanized mice, significantly upregulated the proinflammatory chemokine MIP-1α. However, macrophages showed a significantly reduced amount of CXCL1 (KC) and CCL2 (MCP-1) secretion in CEACAM-humanized versus wt cells. Thus, H. pylori, via the HopQ-CEACAM interaction, controls the production and secretion of chemokines differently in PMNs, macrophages, and DCs. We further show that upon H. pylori contact the oxidative burst of neutrophils and phagocytosis of H. pylori was strongly enhanced, but hCEACAM3/6 expression on neutrophils allowed the extended survival of H. pylori within neutrophils in a HopQ-dependent manner. Finally, we demonstrate that during a chronic mouse infection, H. pylori is able to systemically downregulate hCEACAM1 and hCEACAM6 receptor expression on neutrophils, probably to limit CagA translocation efficiency and most likely gastric pathology. IMPORTANCE Helicobacter pylori is highly adapted to humans and evades host immunity to allow its lifelong colonization. However, the H. pylori mouse model is artificial for H. pylori, and few adapted strains allow gastric colonization. Here, we show that human or CEACAM-humanized, but not mouse neutrophils are manipulated by the H. pylori HopQ-CEACAM interaction. Human CEACAMs are responsible for CagA phosphorylation, activation, and processing in neutrophils, whereas CagA translocation and tyrosine phosphorylation in DCs and macrophages is independent of the HopQ-CEACAM interaction. H. pylori affects the secretion of distinct chemokines in CEACAM-humanized neutrophils and macrophages. Most importantly, human CEACAMs on neutrophils enhance binding, oxidative burst, and phagocytosis of H. pylori and enhance bacterial survival in the phagosome. The H. pylori-CEACAM interaction modulates PMNs to reduce the H. pylori CagA translocation efficiency in vivo and to fine-tune the expression of CEACAM receptors on neutrophils to limit translocation of CagA and gastric pathology.